RANCANG BANGUN SISTEM INFORMASI USAHA MIKRO KECIL MENENGAH STUDI KASUS DINAS KOPERASI UMKM DAERAH ISTIMEWA YOGYAKARTA - Prabowo, Annas Setiawan; Syafirullah, Lutfi (Politeknik Negeri Cilacap, 2018)
Information about UMKM is very much needed by the Cooperative Office of UMKM in determining the direction of MSME development. Accurate data will have the right impact in determining development programs and services for SMEs. The problem that often occurs in managing UMKM data and Consultation is that management is still done manually using a book, so the risk for data loss, double data, and data retrieval are difficult when data is needed quickly. So based on these problems it is necessary to have an Information System to manage MSME data. The method used is the waterfall software development method. The results of this study are systems that can facilitate datamanagement, speed up the data search process, classify according to criteria so that it can be used as a reference in the development and service of MSMEs and assist cooperative service consultants in the business consultation process.